Keberagaman Produk Dan Keputusan Pembelian Terhadap Cafe Do.Pyo - Panji Pramartya; Susana Magdaena Muskita (EBISMA : Jurnal Ekonomi, Bisnis, Manajemen dan Akuntansi, 2025)
Cafe Do Pyo, a popular coffee company in Sorong, has presented a wide range of products to meet various customer preferences. By offering a wide range of products, the company has been able to attract a wide variety of customers and cater to their different needs. This product diversity has allowed companies to stay competitive in a crowded market and maintain their customer loyalty. To maximize product diversity and buyer decisions, Cafe Do Pyo can conduct market research, invest in expanding their product offerings, and invest in promoting the diversity of their products to their customers. By doing these things, the company can remain a successful and competitive coffee company in Sorong.